Peningkatan Hasil Belajar Menggunakan Metode Pembelajaran Inkuiri Terbimbing Terhadap Hasil Belajar Siswa Kelas XI IPS SMA Negeri 1 Slogohimo pada Kompetensi Dasar Kemampuan Mendeskripsikan Kualitas Lingkungan Hidup dan Pembangunan Berwawasan Lingkungan - Muhammad, Trian; , Drs. Suharjo, M.Si (2016)
Train Muhammad/ A 610110058. The Effectiveness of Guided Inquiry Learning Method Usage toward Learning Outcomes in Student XI IPS Class of SMA Negeri 1 Slogohimo On Basic Competence Ability Describing Environmental Quality And Environmental Development. Faculty of Teacher Training and Education. University of Muhammadiyah Surakarta, July, 2016. This study has title "the effectiveness of guided inquiry learning method usage toward learning outcomes in student XI IPS class of SMA Negeri 1 Slogohimo on basic competence ability describing environmental quality and environmental development". The objective of this study was to know that by using guided inquiry learning methods to improve learning outcomes of students geography XI IPS class of SMAN 1 Slogohimo on the basic competence ability to describe the quality of the environment and sustainable development. Pre Experimental Design was used in this study and the type of study design was one-group pretest-posttest design. This study uses only one group or class without comparing with another class in trying out the variable. In this design there is a pretest, before being treated and ends with posttest. Results obtained from this data analysis is hypothesis testing using t test obtained significant value is 0,000 which means that t> t table so Ho rejected and Ha accepted. It can be concluded that the use of guided inquiry learning methods effectively to improve student learning outcomes in XI IPS class of SMA Negeri 1 Slogohimo on basic competence the ability to describe the quality of the environment and sustainable development.